“First, I was stripped; then I was made a man”: body, gender and christian identity in the “Passion of Perpetua and Felicity” - dos Reis Veloso, Wendell (Romanitas - Revista de Estudos Grecolatinos, 2023)
This article proposes a historical analysis of the Passio Sanctarum Perpetuae et Felicitatis, a martyrological narrative from the century III, based on the contributions of Gender Studies. More specifically, we use Joan Scott’s methodological proposal to highlight the elements of the body and gender in the constitution of the social christian identity proposed by the hagiographic discourse analyzed.